1997
DOI: 10.1002/(sici)1098-2264(199709)20:1<60::aid-gcc9>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

NovelMLL-CBP fusion transcript in therapy-related chronic myelomonocytic leukemia with a t(11;16) (q23;p13) chromosome translocation

Abstract: CBP, which is located on 16p13 and encodes a transcriptional adaptor/coactivator protein, has been shown to fuse by the t(8;16)(p11;p13) translocation to MOZ on 8p11 in acute myeloid leukemia. We found a t(11;16)(q23;p13) in a child with therapy‐related chronic myelomonocytic leukemia. Subsequent reverse transcriptase‐polymerase chain reaction and direct sequencing analyses revealed the MLL‐CBP fusion transcript in CMML cells. Because 11q23 translocations involving MLL and t(8;16) involving MOZ and CBP have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 24 publications
1
31
0
1
Order By: Relevance
“…Conversely, MLL-EB1 and MLL-CBP, which are associated with lower Meis1 expression in our model, have only rarely been observed in human AML (a single case for MLL-EB1) (Fu et al 2005). Furthermore, MLL-CBP is associated with human MDS (Satake et al 1997) and induces an MDS-like disorder in mice (J. , which are premalignant conditions characterized by altered self-renewal and differentiation potentials, suggesting that MLL-CBP initiates transformation but does not readily facilitate progression to AML. Thus, MEIS family gene expression levels in subclinical initiated progenitors harboring MLL chromosomal translocations may influence the probability of acquiring necessary secondary mutations for their conversion into LSCs capable of inducing clinical leukemia.…”
Section: Genes and Development 2769mentioning
confidence: 65%
“…Conversely, MLL-EB1 and MLL-CBP, which are associated with lower Meis1 expression in our model, have only rarely been observed in human AML (a single case for MLL-EB1) (Fu et al 2005). Furthermore, MLL-CBP is associated with human MDS (Satake et al 1997) and induces an MDS-like disorder in mice (J. , which are premalignant conditions characterized by altered self-renewal and differentiation potentials, suggesting that MLL-CBP initiates transformation but does not readily facilitate progression to AML. Thus, MEIS family gene expression levels in subclinical initiated progenitors harboring MLL chromosomal translocations may influence the probability of acquiring necessary secondary mutations for their conversion into LSCs capable of inducing clinical leukemia.…”
Section: Genes and Development 2769mentioning
confidence: 65%
“…8 MLL-CBP fusion transcripts have also been detected. 7,9,10 Analyses of the CBP breakpoints in MLL-CBP and CBP-MLL fusion transcripts in two t (11;16) patients revealed that three of the CBP breakpoints exactly correspond to the site of the previously reported t(8;16) breakpoint, while one additional breakpoint was localized further downstream, yet still within the 5′ half of CBP gene. 9 Germline mutations inactivating one CBP allele cause the Rubinstein-Taybi syndrome (RTS).…”
Section: Introductionmentioning
confidence: 80%
“…4,5 Two different somatic translocations involving the CBP gene are found in acute myelogenous leukemia (AML): the t(8;16)(p11;p13.3) and the t(11;16)(q23;p13.3). 4,[6][7][8][9][10] Moreover, constitutional translocations disrupting the CBP gene lead to the Rubinstein-Taybi syndrome (RTS), a complex developmental disorder that among other symptoms, leads to an increased incidence of neoplasia. 5 Of the two leukemia-associated translocations, the t(8;16) is the more common, with an occurrence of four per 1000 AML patients.…”
Section: Introductionmentioning
confidence: 99%
“…Certain genes which encode proteins with HAT activity or potential HAT activity, such as the monocytic leukemia zinc finger protein (MOZ), CREB-binding protein (CBP), p300 and TIF2, are targets of translocations found in AML, myelodysplastic syndrome (MDS) and acute mixed lineage leukemia. [9][10][11][12][13][14][15] The MOZ gene was shown to be fused to the CBP gene and the TIF2 gene in the translocation t(8;16) and inv (8), respectively. [9][10][11] We have found that p300 forms a fusion protein with MLL through the t(11;22) translocation in AML.…”
Section: Introductionmentioning
confidence: 99%